A Comparative Study on Rock Properties in Splitting and Compressive Dynamic Tests - Nan Wu; Zhende Zhu; Yaojun Zhou; Shihu Gao (Shock and Vibration)
The dynamic properties of rock in splitting (tensile) and compressive tests are the focus of rock dynamic mechanics research. In this study, a split Hopkinson pressure bar (SHPB) apparatus was used to assess the comparability and strain rate effect of rock samples under two kinds of load conditions. With an increase in impact velocity under compression and splitting (tensile) tests, the strain rate of the samples increased continuously. The rock properties and strain rate in the two kinds of samples exhibited clear similarities: the dimensionless stress-strain curves of the rock samples were similar under the same strain rates. The peak strength and elastic modulus of the two kinds of samples increased with an increase in the strain rate. The number of cracks increased from intergranular to transgranular failure. The rack initiation value of the two kinds of samples was close at the same strain rate and declined with an increase in the strain rate as evidenced by a power function.